Kell Blood Group System Antigen Genotypic Frequencies in Northern Pakistani Healthy Blood Donors a Multi Center Study - Afsheen Mehmood, Anwar Ul Haq, Khalid Shahab, Hameed Ullah, Muhammad Irfan, Farhan Zeb, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To investigate the genotypic frequencies of the K and K blood group system antigens in Northern Pakistan's healthy blood donors. Material and Method: this Multi center study conducted in department of medicine Hmc Hospital Peshawar From February 2021 to February 2022, The study comprised 59 blood donors in total. The traditional PCR method was used for genotyping, and the amplified products were then run over polyacrylamide gel electrophoresis. Version 26 of SPSS was utilised for the analysis. Results: In this study, 59 blood donors with a mean age of 31.47.07 years were totaled. Male to female ratio was 29.22 to 1. KEL*2/KEL*2 was the most prevalent genotype, found in 53 (91%) donors, followed by KEL*1/KEL*2 in 3 (06%) and KEL*1/KEL*1 in 03 (03%) donors. Conclusion: Identify the antigens in our nation and contrast the findings with those of other populations. The results of this research may be utilised to create a database of genotypic frequencies. Keywords: genotyping, Kell blood group, polymerase chain reaction, and blood donors (PCR).